Strategi Pengembangan Wisata Melalui Program Wisata Industri di Kabupaten Sidoarjo: (Pendekatan Kolaboratif Antara Pemerintah, Pelaku Usaha, dan Masyarakat) - Susi Suharyanti; Zainal Fatah; Amirul Mustofah (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This research examines tourism development strategies through an industrial tourism programme in Sidoarjo Regency as an alternative for regional tourism diversification. Sidoarjo Regency is known as an industrial hub with various production centres, such as shrimp crackers, batik, and shrimp paste (terasi), which have considerable potential to be developed into industrial tourism destinations. The objectives of the study are to analyse industrial tourism development strategies, identify supporting and inhibiting factors, and formulate a collaborative model for sustainable industrial tourism development. The research employs a qualitative approach with data collection techniques including in-depth interviews, participant observation, and documentation study. Research informants include the Sidoarjo Regency Tourism Office, industry stakeholders, tourism communities, and tourists. The results indicate that the industrial tourism development strategy in Sidoarjo utilises a pentahelix approach involving the government, academia, businesses, the community, and the media. Supporting factors include the diversity of local industrial products, good accessibility, and government policy support. However, there are constraints such as minimal digital promotion, limited tourism facilities, and low awareness among business actors regarding the concept of industrial tourism. The recommended collaborative model encompasses institutional strengthening, increasing Human Resources (HR) capacity, developing supporting infrastructure, innovating tourism products, and integrated digital marketing. This research provides a practical contribution to the development of industrial tourism in regions with a strong small and medium-sized industrial economic base.